The role of arbitration in the resolution of international commercial disputes - Eishan Jan, Mohammad Naqib (2013)
International commercial arbitration, as one of the most effective methods of dispute resolution, has evolved with the evolution of international commerce and the associated disputes that arise from it. In this paper attempt is made to explain the systems and procedures applicable to international commercial arbitration and helps international entrepreneurs or business people to understand what is international commercial arbitration, how it differs from other forms of dispute resolution and what are its characteristics? The paper further discuss issues relating to the agreement to arbitrate, ad hoc and institutional arbitrations, selection of arbitrator or arbitral panel, the arbitrator’s jurisdiction, awards and the enforcement of the arbitration award. In discussing these issues the paper refers to relevant international conventions and various international organizations that engage in or regulate international commercial arbitration around the world.